Increasing Environmental Awareness and Early Response to Landslide Disasters in Hilly Slope Areas (Pasirmunjul Village, Sukatani District, Purwakarta) - Lina Sukanti (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This community service program aims to raise environmental awareness and enhance early landslide disaster mitigation among residents living in hillside areas, specifically in Pasirmunjul Village, Sukatani District, Purwakarta. The activities were carried out through an educational and participatory approach involving awareness campaigns, training sessions, and disaster response simulations. The target participants included local villagers, community leaders, and youth groups who were empowered as agents of change. The results indicate a significant improvement in public understanding of landslide risk factors, the importance of environmental conservation, and practical preventive measures that can be implemented individually or collectively. Furthermore, the program facilitated the establishment of a community-based disaster preparedness team, enhancing the village's readiness and resilience in the face of potential disasters. This initiative serves as a foundational step toward fostering a disaster-aware culture and promoting a safer, more sustainable environment in landslide-prone regions.